Pengaruh Penggunaan Aplikasi Binmas Online System Versi 2.0 (BOS V2) Terhadap Efektivitas Kerja Bhabinkamtibmas : Studi Polres Tangerang Selatan - Rachmat, Agam Tsaani; Prisgunanto, Ilham; Sibarani, Bernard; Dhamayanti, Sylvia Kartika (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2024)
The aim of this research is to determine the effect of using the Binmas Online System version 2.0 (BOS V2) application on the work effectiveness of the South Tangerang Police Department's Bhabinkamtibmas. There are two theories used in this research, namely (1) David's Technology Acceptance Model (TAM) theory and (2) Siswanto's Work Effectiveness theory. This research uses a quantitative approach with survey methods. The population in this study was 95 people using total sampling. The data collection technique used was a questionnaire. The data analysis technique in this research uses instrument testing, assumption testing, hypothesis testing, and continued with regression testing. The results of the research show that the use of the BOS V2 application has a positive effect on the work effectiveness of the South Tangerang Police Department's Bhabinkamtibmas with tcount (13.334), (6.240) > ttable (1.998). Next, Fcount (38.955) > Ftable (2.45) and the regression equation ? = 3.048 + 0.353X. The conclusion of this research is that the use of the BOS V2 application has a significant effect on the work effectiveness of the South Tangerang Police Department's Bhabinkamtibmas. Thus, the BOS V2 application has an impact on the work effectiveness of Bhabinkamtibmas. The use of the BOS V2 application by the South Tangerang Police Bhabinkamtibas has been running optimally so that it has an impact on the effectiveness of Bhabinkamtibmas' work itself so that it can support every report and task given so that it runs optimally.